An in vitro study of fluoride-preloaded halloysite nanotubes to enhance the fluoride release in conventional and resin-modified glass ionomer cements - Martha Esperanza García-Moreno; Elias Nahum Salmerón-Valdés; Adriana Alejandra Morales-Valenzuela; Ulises Velázquez-Enríquez; Víctor Hugo Toral-Rizo; Edith Lara-Carrillo (Saudi Dental Journal)
Objective: The purpose of the study was to compare the fluoride release in two conventional glass ionomer cements (Ionobond, Ketac Molar) and two resin-modified glass ionomer cements (Vitrebond, Fuji II LC) adapted with halloysite nanotubes preloaded with sodium fluoride at different concentrations. Methods: In total, 96 samples were prepared and distributed into four control groups and eight experimental groups (5 % and 10 %). Totals of 10 % and 5 % of the total weight of ionomer powder needed to prepare the samples were replaced with nanotubes, preloaded at 2,000 parts per million, respectively. The experimental groups were followed for 120 days at seven time intervals. All the samples were stored at 37 °C. Results: All the experimental groups showed significant differences compared with the control groups; likewise, differences were observed between the concentrations of 5% and 10%. Conclusion: The experimental groups (conventional and resin-modified glass ionomer cements adapted with preloaded nanotubes) released a higher and more constant amount of fluoride compared to the control groups.